Pendidikan Multikultural: Dalam Perspektif Filsafat Pendidikan Islam - Citra Partika Dwi; Desi Nurlita; Azizah Hanum (Universitas Palangka Raya, 2024)
Thisi researchi aimsi toi analyzei multiculturali educationi fromi thei perspectivei ofi Islamici educationali philosophy.i Thisi researchi usesi ai qualitativei researchi methodi basedi oni libraryi research.i Thei maini sourcei fori thisi researchi isi Islamici educationali literaturei basedi oni philosophy.i Thei naturei ofi thisi researchi itselfi isi descriptive-i analysis.i Thei datai collectioni techniquei ini thisi researchi usesi thei libraryi researchi method,i namelyi libraryi study.i Thei resulti ofi thisi writingi isi thati educationi isi ai processi ofi humanizingi humansi soi thati humansi arei expectedi toi bei ablei toi understandi themselves,i otheri people,i naturei andi theiri culturali environment.i Educationi andi multiculturalismi arei solutionsi toi diversei culturali realitiesi asi ai processi ofi developingi alli potentiali thati respectsi pluralityi andi heterogeneity.i Thei essencei ofi multiculturalismi isi culturei andi recognitioni ofi culturali diversityi asi welli asi ai responsei toi acceptingi diversei culturali realities.i Islami isi ai religioni thati isi noti basedi oni culture,i buti hasi ai concepti ofi howi itsi peoplei arei culturedi andi havei goodi morals.i Islamici culturei isi ai procedurei thati refersi toi Islamici principles.i Islamici culturei itselfi isi purelyi basedi oni thei Korani andi Hadith.